Transmission of a Novel Imprinting Center Deletion Associated With Prader–Willi Syndrome Through Three Generations of a Chinese Family: Case Presentation, Differential Diagnosis, and a Lesson Worth Thinking About - Zhang, Kaihui; Liu, Shu; Gu, Wenjun; Lv, Yuqiang; Yu, Haihua; Gao, Min; Wang, Dong; Zhao, Jianyuan; Li, Xiaoying; Gai, Zhongtao; Zhao, Shimin; Liu, Yi; et al. (Frontiers in Genetics, 2021)
Prader-Willi syndrome (PWS) is a complex genetic syndrome caused by the loss of function of genes in 15q11-q13 which are subject to regulation by genomic imprinting and expressed from the paternal allele only. The main clinical features of PWS patients are hypotonia during the neonatal and infantile stage, accompanied by delayed neuropsychomotor development, hyperphagia, obesity, hypogonadism, short stature, and so on. However, PWS has a clinical overlap with other diseases, especially those with other gene variations or chromosomal imbalances but sharing part of the similar clinical manifestations with PWS, which is defined as Prader-Willi-like syndrome (PWLS). Further, it is worth mentioning that significant obesity as a consequence of hyperphagia in PWS usually developed between the ages of 1 and 6 years, which makes early diagnosis difficult. Thus, PWS is often not clinically recognized in infants and, on the other hand, may be wrongly suspected in obese and mentally deficient patients. Therefore, an accurate investigation is necessary to differentiate classical PWS from PWLS phenotype, which is imperative for further treatment. For PWS, it is usually sporadic, and very rare family history and affected siblings have been described. Here, we report the clinical and molecular findings in a three-generation-family with a novel 400 kb microdeletion affecting the chromosome 15 imprinting center (IC). Overall, the present study finds that the symptoms of our patient are distinct from, and more severe than, those of typical PWS cases. The familial occurrence and atypical clinical features were overwhelming to our diagnostic strategy. The microdeletion included region within the complex small nuclear ribonucleoprotein polypeptide protein N (SNRPN) gene locus encompassing the PWS IC, and was identified by using a variety of techniques. Haplotype studies suggest that the IC microdeletion was vertically transmitted from unaffected paternal grandmother to unaffected father, and then caused PWS in two sibling grandchildren when the IC microdeletion was inherited paternally. Based on the results of our study, preimplantation genetic diagnosis (PGD) was applied successfully to exclude imprinting deficiency in preimplantation embryos. Our study may be especially instructive with regard to accurate diagnosis, differential diagnosis, genetic counselling, treatment, and eugenics for familial PWS patients.